The Effect of Traditional and Stabilization-Oriented Exercises on Deep Stabilization System Function in Elite Futsal Players - Jebavy, Radim; Baláš, Jiří; Vomackova, Helena; Szarzec, Jakub; Stastny, Petr (Sports (Basel, Switzerland), 2020)
BACKGROUND: This study aimed to compare the effect of traditional and stability-oriented strength exercises on trunk stability and deep stabilization system (DSS) activation in elite futsal players. METHODS: Twenty elite futsal players (21-34 years, 180 ± 13 cm, 79 ± 15 kg) were randomly divided into a group that performed stability-oriented exercises and a group that performed traditional strength exercises. Both interventions lasted for 10 weeks and included 25 strength training sessions. MAIN OUTCOME MEASURES: The DSS pretest and posttest included the diaphragm test, trunk flexion test, back extension test, hip flexion test, intraabdominal pressure test, and a side plank test on a 1-5 point scale. RESULTS: Both groups had similar initial test results, where the stability-oriented exercise group had significantly improved intraabdominal pressure test (p = 0.004, by lower quartile rate), trunk flexion (p = 0.036, by 0.5 grade in median), and side plank (p = 0.002, by 1 grade in median) in posttest results. Traditional exercise did not change the results of any of the included DSS function tests. CONCLUSIONS: Stabilization-oriented exercises effectively activate the functions of the DSS and should be prioritized over traditional strength exercises in injury prevention training programs. The use of stabilization-oriented exercises might prevent injury and overloading in elite futsal players.
Keywords: complex exercises; trunk stability; injury prevention; strength training